2023
DOI: 10.3390/agriculture13040755
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Vegetables and Fish with Rice in Rain-Fed Farmland: Towards Sustainable Agriculture

Abstract: Sustainability in aquaculture or agriculture production is depended on its successive use of natural resources that can ensure economic increment and sustainability of the livelihood of people. The objective of the study was to find out suitable combination of rice-fish-vegetable to be cultured in rainfed rice field. Two experiments were conducted for 4 months under rainfed condition. Two rice varieties (BRRI-51 and BRRI-52), three different fish species. i.e., Cyprinus carpio var. communis, Barbonymus goniono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…To increase output in farm produce, there is a need to have a competitive advantage. With the increase in various innovative technologies, more recent studies have considered a competitive advantage in some agricultural businesses (Wang et al 2021;Pan et al 2021;Jewel et al 2023;Anzaku and Salau 2017). Different technological models have been developed on sustainable development and economic development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase output in farm produce, there is a need to have a competitive advantage. With the increase in various innovative technologies, more recent studies have considered a competitive advantage in some agricultural businesses (Wang et al 2021;Pan et al 2021;Jewel et al 2023;Anzaku and Salau 2017). Different technological models have been developed on sustainable development and economic development.…”
Section: Introductionmentioning
confidence: 99%
“…It goes beyond simply focusing on the financial aspects of farming and considers the thoughtful and effective use of non-renewable resources, contributing to the growth of nutritious and healthy food while improving the standard of living for farmers By categorisation; the main categories of sustainability are economic, environmental, and social. Some background is also necessary on the sustainability of the farming practice (Pan et al 2021;Jewel et al 2023;Aluwani 2023;Ngobeni and Muchopa 2022). These studies have identified various sustainable approaches that could be adopted in agricultural farming.…”
Section: Introductionmentioning
confidence: 99%